PERBANDINGAN HUBUNGAN KEPEMIMPINAN SITUASIONAL DENGAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA KARYAWAN PADA BANK PANIN KCU BOGOR DAN PEGAWAI NEGERI SIPIL KECAMATAN BOGOR UTARA - Hari Muharam (Universitas Pakuan, 2015)
This study aims to analyze the relationship Situational Leadership and Transformational Leadership on Job Satisfaction of employees at Panin Bank KCU Civil Servants Bogor and Bogor subdistrict North.The study population was all employees Panin Bank KCU Bogor with a population of about 138 employees with the sample used as many as 103 respondents. The sampling technique using Proportional Random Sampling technique. While the study population at the Civil District of North Bogor amounted to 107 employees with the sample used as many as 85 employees. The sampling technique by using Simple Random Sampling. Data were analyzed using regression analysis.The results show that: First, the closeness of the relationship between situational leadership and job satisfaction of Panin Bank KCU Bogor obtained correlation coefficient of 0.578 means the closeness of the relationship was. The closeness of the relationship between transformational leadership and job satisfaction of Panin Bank KCU Bogor obtained correlation coefficient of 0.607 means the closeness of the relationship was. The relationship between situational leadership and transformational leadership together with job satisfaction at Panin Bank KCU Bogor correlation coefficient means that the relationship of closeness 0,641 strong. Second, the closeness of the relationship between situational leadership and job satisfaction of the Civil Service District of North Bogor obtained correlation coefficient of 0.616 means keerata strong relationship. The closeness of the relationship between transformational leadership and job satisfaction of the Civil Service District of North Bogor obtained correlation coefficient of 0.639 means the closeness of the relationship strong. The relationship between situational leadership and transformational leadership together with job satisfaction in the Civil District of North Bogor obtained correlation coefficient of 0.756 means the closeness of the relationship strong.Keywords: Situational Leadership, Transformational Leadership and Job Satisfaction